279. CLONAL RELATIONSHIP AND ALCOHOL CONSUMPTION-ASSOCIATED MUTATIONAL SIGNATURE IN SYNCHRONOUS HYPOPHARYNGEAL TUMORS AND ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Ko, Josephine
Abstract: The patients with dual esophageal squamous cell carcinoma (ESCC) and head and neck cancers have poor prognosis, but the underlying genetic pathogenesis is unclear. We hypothesize that independent origin rather than multifocality, which means local or lateral spreading involves the development of synchronous ESCC and hypopharyngeal cancer (HPC). We also hypothesize that multi-regional assessment provides better understanding of the evolution of tumor subclones and assessment of intra-tumor heterogeneity to guide personalized treatment with prognostic implications. Multiple region whole-exome sequencing (M-WES) and clonality analysis were used to assess clonal relationship and spatial inter- or intra-tumor heterogeneity (ITH) in 62 tumor regions, six normal tissues, and 15 blood samples from eight dual ESCC/HPC and ten ESCC patients. All synchronous ESCC/HPC patients had COSMIC 16 mutation signature compared to only 40% ESCC in the current study (p = 0.013) and public ESCC dataset (n = 165, p = 0.003). The mutational landscape and copy number variation (CNV) profiles were completely distinct between the ESCC/HPC; clonality analysis further suggested the two primary tumors shared no or only one clone accompanying independent subclone evolution. The M-WES strategy demonstrated higher sensitivity and accuracy for detection of mutational prevalence and the late branch mutations among different regions in the ESCC tumors compared to traditional single biopsy strategy. Patients with high ITH was significantly associated with both relapse and survival. Our hypothesis-generating M-WES ITH assessment data have implications for prognostication. We are the first to show a distinctive CNV and genetic mutation profile, the predominant alcohol-related COSMIC 16 mutational signature in synchronous ESCC/HPC, providing genetic evidence for a multi-centric independent origin for clonal evolution and the theory of field cancerization implicating an etiologic role of alcohol metabolism in dual ESCC/HPC carcinogenesis.